Kierkegaard in golden-age Denmark - Kirmmse, Bruce H. (Indiana series in the philosophy of religion., 1990)
Against the background of Denmark's evolution from a mercantile economy to a broad-based agricultural economy, Kirmmse reinterprets Kierkegaard's thought as a reaction to the tensions within his society.